Types and Characteristics of Leadership: A Qur’anic Presentation - Khan, Musaddiq Majid (Pusat Pengembangan Integrasi Ilmu Naqli & Aqli (PIINA), 2017)
Leadership is one of the integral parts of human life because human nature is universally imbued with cooperation and mutual assistance. It is the leadership which establishes the firm relations among the people and elucidates the different ways towards the progressive development of civilizations. Leadership, in contemporary times, is being claimed by the people who themselves do not have ability to lead. In fact such persons do not have even the basic knowledge about the leadership. Communities developing under such leadership are like blind followers, like mass who do not understand their role in their respective communities. This is also one of the factors for fall of civilizations. Quran speaks about the leadership in details, gives examples of leadership in both; good and bad aspects and their impacts on the societies. This article will explain the types and characteristics of leadership as mentioned in the Quran. It is hoped that this article will present a clear and explicit view of Quran towards the leadership. It will also explain the ingredients and characteristics of the successful leadership which will exhibit the distinguished approach of the Quran in dealing with different aspects of the leadership. Because of the limitation of time and space in this article only Qiyādah Al-Rāshidah and its ethical characteristics will be discussed.